Theoretical evaluation of abrasive wear behavior of B4C/ FeCrC coating layer evaluated by a Taguchi approach - Gur, Ali Kaya; Yildiz, Tulay; Icen, Busra (Walter de Gruyter Gmbh, 2020)
In this study, B4C and FeCrC powders were alloyed on the surface of AISI 430 by a fusion process via plasma transferred arc welding. Mixtures of these powders at various amounts were used. The microstructure and wear behavior of the obtained coating layers were investigated. The wear behavior of the coating layers was planned using the Taguchi method. Abrasive wear mass loss results were optimized with the smaller the better control characteristic of the Taguchi method, and the results were analyzed graphically. The actual data obtained at the end of the study were formed by using an L-16 (4 x 2, 2 x 2) mixed array, and the remaining wear rates were calculated with the help of theoretical formulas in order to obtain theoretical abrasive wear results.
Keywords: PTA weld-surfacing process; B4C/FeCrC; wear; theoretical evaluation; Taguchi